Geochronology of granulitized eclogite from the Ama Drime Massif: Implications for the tectonic evolution of the South Tibetan Himalaya - Cottle, J; Jessup, M; Newell, D; Horstwood, M; Noble, SR; Parrish, R; Waters, D; Searle, M (2009)
[1] The Ama Drime Massif (ADM) is an elongate north-south trending antiformal feature that extends ∼70 km north across the crest of the South Tibetan Himalaya and offsets the position of the South Tibetan Detachment system. A detailed U(-Th)-Pb geochronologic study of granulitized mafic eclogites and associated rocks from the footwall of the ADM yields important insights into the middle to late Miocene tectonic evolution of the Himalayan orogen. The mafic igneous precursor to the granulitized eclogites is 986.6 ± 1.8 Ma and was intruded into the paleoproterozoic (1799 ± 9 Ma) Ama Drime orthogneiss, the latter being similar in age to rocks previously assigned to the Lesser Himalayan Series in the Himalayan foreland. The original eclogite-facies mineral assemblage in the mafic rocks has been strongly overprinted by granulite facies metamorphism at 750°C and 0.7-0.8 GPa. In the host Ama Drime orthogneiss, the granulite event is correlated with synkinematic sillimanite-grade metamorphism and muscovite dehydration melting. Monazite and xenotime ages indicate that the granulite metamorphism and associated anatexis occurred at <13.2 ± 1.4 Ma. High-grade metamorphism was followed by postkinematic leucogranite dyke emplacement at 11.6 ± 0.4 Ma. This integrated data set indicates that high-temperature metamorphism, decompression, and exhumation of the ADM postdates mid-Miocene south directed midcrustal extrusion and is kinematically linked to orogen-parallel extension. Copyright 2009 by the American Geophysical Union.